[RETRACTED ARTICLE] Therapeutic Penetrating Keratoplasty for Severe Fungal Keratitis in a Thai Tertiary Care Center - Kengpunpanich, Sathiya; Prabhasawat, Pinnita; Gem, Chencho; Chirapapaisan , Chareenun; Booranapong , Wipawee; Ngowyutagon , Panotsom (Siriraj Medical Journal, 2023)
Objective: To evaluate the outcomes of therapeutic penetrating keratoplasty (TPK) performed for severe fungal keratitis. Materials and Methods: Medical records of all patients who underwent TPK in Siriraj Medical Center between April 2010 and July 2020 were culled, and those in which fungal pathogens were definitively identified were studied. Patient records with follow up less than three months were excluded. Patient demographic data, outcome measures and complications following TPK were recorded. The primary outcome was eradication of the fungal infection. Secondary outcomes were preservation of anatomical integrity, graft survival and achievement of visual acuity (VA) greater than or equal to 3/60. Results: Sixty patients met the study criteria and were included in the analysis. The mean patient age was 56 (range: 23-79) years, and most patients were men (46, 77%). The mean follows up time was 30.87 months (range1.61-122.71). Fifteen eyes (25%) sustained corneal perforation before undergoing TPK. Graft survival was 30% at 1 year, 18% at 5 years, and 11% at 10 years. The most common organism was fusarium (23 patients, 38%). The median duration from presentation to surgery was 14 (8-21) days. Disease eradication was achieved in 44 patients (73%) and VA better than 3/60 was achieved in 14 (23%). Anatomical integrity was maintained in 46 (76%) eyes. Repeat PKP was performed in 15 patients (25%), most commonly for recurrent infection. Conclusion: TPK offers a good chance of disease eradication and maintenance of anatomical globe integrity and is a reasonable therapeutic option in patients with severe fungal infection.